THE ANALYSIS OF ARTIFICIAL INSEMINATION SUCCESS ON BALI CATTLE AT KARANGASEM REGENCY - I G. L., SWASTIKA; INGGRIATI, N. W. T.; ADI PUTRA, I G. S. (Majalah Ilmiah Peternakan, 2018)
is the most potential livestock sector of cattle at Karangasem because this regency has their biggest population in Bali. Their population in 2016 achieved 127.589 (22.35%) from the total population in Bali. artificial insemination (AI) is one of the cattle development programs to support their population, quality, and production. This research aims at finding farmers perception, motivation, knowledge, attitude and technical skill on cattle AI. It aims at analyzing the influence of knowledge, attitude and technical skill of farmers on AI. These are used in order to motivate the AI program. This study was using a survey research with questionnaires for data collection at eight sub-districts of Karangasem regency with 104 selected respondents. Analysis of data was using path and descriptive analysis. The results showed that farmers with high knowledge, positive attitude, high technical skills, their perception to conduct AI program in highland were strong. It can be concluded that farmers’ knowledge, attitude, and positive technical skills gave significant influences to the perception of farmers of AI. The level of AI implementation is categorized success at Karangasem regency.